2018
DOI: 10.1093/brain/awy241
|View full text |Cite
|
Sign up to set email alerts
|

A feedback loop between dipeptide-repeat protein, TDP-43 and karyopherin-α mediates C9orf72-related neurodegeneration

Abstract: TDP-43 accumulation is a major pathological hallmark of amyotrophic lateral sclerosis and frontotemporal dementia, including the most common genetic cause, G4C2 hexanucleotide repeat expansion in C9ORF72 (C9ALS/FTD). Solomon et al. report that G4C2-derived dipeptide repeat protein but not G4C2-RNA accumulation causes TDP-43 proteinopathy that triggers onset and progression of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 57 publications
9
102
0
Order By: Relevance
“…Among the DPR proteins, poly‐GA has been most robustly linked to TDP‐43 aggregation in vitro , although the mechanism is still unknown (Schludi et al , ; Khosravi et al , ; Lee et al , ; Nonaka et al , ; Solomon et al , ). We co‐expressed all DPRs with the aggregation‐prone CTF of TDP‐43 tagged with RFP.…”
Section: Resultsmentioning
confidence: 99%
“…Among the DPR proteins, poly‐GA has been most robustly linked to TDP‐43 aggregation in vitro , although the mechanism is still unknown (Schludi et al , ; Khosravi et al , ; Lee et al , ; Nonaka et al , ; Solomon et al , ). We co‐expressed all DPRs with the aggregation‐prone CTF of TDP‐43 tagged with RFP.…”
Section: Resultsmentioning
confidence: 99%
“…Although described in C9orf72 ALS iPSC-derived neurons [170], colocalization of RanGAP1 puncta with RNA foci has yet to be reported in patient tissues. A recent study observed nuclear depletion and cytosolic accumulation of KPNA4, a member of karyopherin-α family involved in the nuclear import pathway, in the frontal cortex of sporadic and C9orf72 -FTD/ALS, with the phenotype being more pronounced in patients with the C9orf72 expansion [134]. This nuclear depletion was observed in neurons with and without sense-encoded DPR or phosphorylated TDP-43 inclusions.…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
“…Surprisingly, although there is evidence for the association of poly(GR) with nucleolar stress, nucleocytoplasmic transport dysfunction and nuclear membrane integrity in cell models and patient tissue [86,[96][97][98][99], no evidence for these pathways was observed in this study. However, in Drosophila, expression of both (GR) 64 and (GA) 64 could cause the mislocalization of its homologues of TDP-43 and karyopherins 2 and 4 [100].…”
Section: C9orf72mentioning
confidence: 99%